2011
DOI: 10.1111/j.1600-0501.2011.02329.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on the association between genetic predisposition and dental implant biological complications

Abstract: Methodological and study design issues restricted the possibility to draw robust conclusions. Within the limits of this review, it might be concluded that there is no obvious association between specific genetic polymorphism and dental implant failure in terms of biological complications, although a tendency should be underlined showing the potential link between IL-1 genotype and peri-implantitis. Well designed and adequately powered prospective cohort studies are needed to provide further information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 62 publications
(214 reference statements)
3
73
0
3
Order By: Relevance
“…[74][75][76] However, in a systematic review, Dereka and colleagues 77 reported no apparent association between specific genetic polymorphism and dental implant failure in terms of biological complications (peri-implant diseases). Hultin and colleagues, 78 Rogers and colleagues, 79 and Campos and colleagues 80 also reported no association between gene polymorphism and peri-implantitis.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…[74][75][76] However, in a systematic review, Dereka and colleagues 77 reported no apparent association between specific genetic polymorphism and dental implant failure in terms of biological complications (peri-implant diseases). Hultin and colleagues, 78 Rogers and colleagues, 79 and Campos and colleagues 80 also reported no association between gene polymorphism and peri-implantitis.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…A recent systematic review of the association between genetic predisposition and biological complications of dental implants suggested that there is no strong association among specific genetic polymorphisms (IL-1A, IL-1B, IL-17RC) and peri-implantitis, although there was a notable tendency indicating a link between the IL-1 genotype and peri-implantitis [19], [20]. Another study presented MMP-8 and PGE-2, both regulated by IL-1 as possible genetic markers for unsuccessful implants based on their role in regulating the extra cellular matrix (ECM) which may enhance bone healing within defects and promote implant osseointegration [21].…”
Section: Introductionmentioning
confidence: 99%
“…Various prospective and retrospective analyses have shown that the systemic health of the host (e.g., type II diabetes mellitus) [25], genetic traits [26], environmental factors (e.g., smoking) [27,28], a past history of periodontitis [28], poor compliance with mechanical cleaning recommendations [27], and infrequent dental maintenance visits [29] is major risk factors for the development of peri-implantitis.…”
Section: Biofilm-induced Peri-implant Diseasesmentioning
confidence: 99%